A computerised data base for the diagnosis of rare dysmorphic syndromes. Issue 2 (April 1984) - Winter, R M; Baraitser, M; Douglas, J M
Abstract : A system is described for the computerised storage and retrieval of information on rare dysmorphic syndromes. The clinician can ask a microcomputer for a list of syndromes with any logical combination of physical abnormalities. A descriptive title and full references are also provided on request. Similar systems would be applicable to other medical specialties.